Determination of Land Suitability Criteria for Maize Hybrid in Boalemo Regency Based on Optimum Yield and Selected Land Quality - null Nurdin; Asda Rauf; Yunnita Rahim; Echan Adam; Nikmah Musa; Fitriah Suryani Jamin; Suyono Dude; Rival Rahman; Hidayat Arismunandar Katili (Applied and Environmental Soil Science)
The significant effect of land quality on maize production has not been fully considered in the existing land suitability criteria. Therefore, this study aims to determine land suitability criteria for hybrid maize in Boalemo Regency based on the optimum yield and land quality. It was carried out in Boalemo Regency, Indonesia, where the land unit of 67 units was surveyed to obtain land characteristics data. A partial least square of structural equation model (PLS-SEM) with SmartPLS 8.0 was used to select a robust land quality controlling hybrid maize yield, while the boundary line method was used to determine optimum yield and differentiating of land suitability criteria. The result showed that land qualities that define the optimum yield of hybrid maize were root conditions, nutrient availability, nutrient retentions, land preparation, and erosion hazard. The soil characteristics were effective depth, coarse material, organic C, total N, K exchangeable, slopes, soil erosion, rock outcrops, and surface rocks. Furthermore, the highest optimum yield of 8.54 ton/ha was achieved by the total N and slopes for a very suitable class (S1), while the lowest of 5.58 ton/ha was obtained by exchangeable K for class S1. This showed that the combination of PLS-SEM and boundary line analysis was a better approach to developing new land suitability criteria for hybrid maize.